Taking the TOEIC® 2: - Anderson, Peggy (2016)
Taking the TOEIC 2: Skills and Strategies is designed for pre-intermediate students of Engish who need to start preparation for the TOEIC Listening and Reading test. The book is divided into sections dealing with the areas tested in the TOEIC: listening, grammar, and reading. Each grammar unit in Chapter 2 deals with different grammar points that most commonly appear in the actual TOEIC test and provides grammar and vocabulary exercises based on the specific points dealt with in each unit. The mini-tests in each chapter of the book follow the same style and format as the actual TOEIC test. The final chapter of the book is a full-length practice test, giving students the opportunity to put into practice what they have learned in the previous chapters.